Development of maritime tourism port valorization sustainable Matahari Terbit Sanur Bali - Amrullah, Romanda Annas; Nofandi, Faris; Prayitno, Prayitno (Priviet Social Sciences Journal, 2023)
Tourism is the fastest growing and emerging sector after the Covid-19 pandemic ended. However, there has been no maritime tourism port specifically built in Indonesia, even though Indonesia is known as an archipelagic country and the world's maritime axis. The development of coastal areas (especially the Sunrise Maritime Tourism Port in Sanur, Bali) is very important as a tourist attraction and as a model for other areas that have coastal areas. The concept of integrating maritime education, business centers, tourism with cultural performances and the use of environmentally friendly technology but still in the corridor of maintaining environmental, social and economic sustainability so as to create a superior port. This research uses qualitative research methods, PRISMA and PICOS data analysis techniques. Develop and integrate two theories; sustainable development goals with Systematization of the development to produce the concept of Sustainable Valorization Novelty.